Sex modifies association between dietary sodium intake and cardiovascular disease mortality among US adult with hypertension: a national population-based cohort - Chen, Zhiqiang; Rao, Jingan; Fan, Weiguo; Wu, Zuxiang; Shi, Yumeng; Wu, Yingxing; Hu, Huan; Cheng, Xiaoshu; Li, Ping (Frontiers in Cardiovascular Medicine, 2024)
ObjectivesThe objective of this study was to examine the relationship between dietary sodium intake and cardiovascular disease (CVD) mortality in hypertensive American adults.MethodsA prospective cohort study was conducted to examine the association between dietary sodium intake, as estimated by a single 24-h dietary recall from the National Health and Nutrition Examination Survey (2003–2012), and mortality data obtained from the National Death Index.ResultsThis study included 12,236 adults with hypertension, with 837 CVD-related deaths identified over a median follow-up period of 10.3 years. A nonlinear association between dietary sodium intake and CVD mortality was observed. The inflection point of the curve occurred at a sodium intake level of 2.07 g/day. Below this threshold, higher sodium intake was associated with a reduced risk of CVD mortality, though the association was not statistically significant after full adjustment (aHR: 0.78, 95% CI: 0.58–1.05). In contrast, sodium intake above 2.07 g/day was significantly associated with an increased risk of CVD mortality (aHR: 1.12, 95% CI: 1.02–1.23). The log-likelihood ratio test yielded a P-value of 0.04. This J-shaped association was observed exclusively in females, not males. Among females, the adjusted hazard ratios (95% CI) were 0.65 (0.42, 0.99) below and 1.29 (1.11, 1.53) above the inflection point (P for log-likelihood ratio test = 0.009).ConclusionsIn American adults with hypertension, dietary sodium intake exceeding 2.07 g/day was significantly associated with an increased risk of CVD mortality, while intake below this threshold was not significantly linked to mortality risk. Additionally, a sex-specific effect of dietary sodium intake on CVD mortality was observed, showing a J-shaped relationship exclusively in females, with no such association found in males.